UPAYA PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MELIPAT ORIGAMI DI KELOMPOK B TK PAUD NUSANTARA GOWA - Sarmila Sarmila; Nur Khalisah Latucosinah; Ade Agusriani (Universitas Muhammadiyah Metro, 2023)
One activity that can improve children's fine motor skills is folding origami paper. Folding origami paper is a technique for creating arts or crafts which are generally made from paper with the aim of producing various forms of toys, decorations and other creative forms. This research aims to determine the improvement of children's fine motor skills through origami folding activities in group B of the Nusantara Gowa PAUD Kindergarten. The instruments used were observation instruments to assess students' fine motor development during folding activities and interview guides as tools for researchers in obtaining additional data that had not been obtained through observation. The results of the research concluded that paper folding activities can improve children's fine motor skills at the Nusantara Gowa PAUD Kindergarten with good results. This can be seen from the development of students' fine motor skills, where in the pre-cycle research it can be seen that students reached 37%, then in cycle I there was an increase of 73%, and in cycle II there was an increase of 87%. These results show that this research was successful because it had reached the research indicator of 75%.